The political economy of import substitution in the 21st century: The challenge of recapturing the domestic market in Rwanda - Pritish Behuria (London School of Economics and Political Science (LSE), Department of International Development, 2017)
Import substitution has been marginalised from development policy discourse since the 1970s. This paper examines the Rwandan government's recent attempt at reintroducing industrial policy with some attention devoted to 'recapturing the domestic market' - a term used to replace the ignominy associated with 'import substitution.' The paper examines two cases - cement and textiles - where such policies have been recently established in Rwanda. The paper argues that any attempt at recapturing the domestic market will require a strategy close to the policies of East Asian developmental states in terms of 'picking winners.' However, strategically maintaining reciprocity through state-business relationships is only part of the challenge. Though foreign investors have been leant on initially, actions must be put in place to develop local capitalist partners who may step in if foreign investors leave once incentives are reduced. This is further complicated by the government's failure to develop partnerships with existing local capitalist partners. The Rwandan government is also constrained by a small market size. Any attempt at import substitution must occur in the context of accessing larger markets through the East African Community (EAC). This paper demonstrates that such regional trade agreements constitute a much greater constraint on the use of industrial policy than multilateral trade agreements or bilateral trade agreements with the United States of America or European countries (although pressure from donors may also contribute to reducing policy space). Such challenges showcase how the Rwandan government has sought to build reciprocal control mechanisms while attempting to access large markets through regional integration. Though the Rwandan government has made some progress recently, state intervention is required to reintroduce import substitution in the 21st century and must be balanced by the need to meet domestic and international political constraints.
Keywords: 330; Import substitution; Industrial Policy; Rwanda; political economy; textiles; cement